Magnetic Susceptibility of Tetrahedrally Bonded Amorphous Semiconductors - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
A special theoretical formulation on the magnetic susceptibility of tetrahedral amorphous semiconductors is proposed. This formulation is based upon a Wannier representation involving two terms: a diamagnetic term and a paramagnetic contribution. In addition, electron-spin resonance referred to amorphous silicon is considered.